What drives the attentional bias for fearful faces? An eye‐tracking investigation of 7‐month‐old infants' visual scanning patterns. (21st June 2020) - Segal, Shira C.; Moulson, Margaret C.
Abstract: Seven‐month‐old infants display a robust attentional bias for fearful faces; however, the mechanisms driving this bias remain unclear. The objective of the current study was to replicate the attentional bias for fearful faces and to investigate how infants' online scanning patterns relate to this preference. Infants' visual scanning patterns toward fearful and happy faces were captured using eye tracking in a paired‐preference task, specifically exploring if the fear preference is driven by increased attention to particular facial features. Infants allocated increased attention toward the fearful face compared to the happy face overall, thus successfully replicating the attentional bias, and greater attention toward the fearful eyes was associated with a greater magnitude of the fear preference. The current findings suggest that the fearful eyes are a salient facial feature in capturing infants' attention toward the fearful face and that increased scanning of the fearful eyes may be one mechanism driving the overall fear preference. In addition, scanning patterns, and attention to critical features specifically, are highlighted as a strategy for examining the mechanisms underlying the development of emotion recognition abilities in infancy.